Kampanye Kreatif Iklan “Bleh Sabbath” pada Brand Pakaian - Wanda Vernando; Indri Rachmawati (Bandung Conference Series: Communication Management, 2022)
Abstract. In the 21st century, especially business actors are required to be able to keep up with the times, innovative, and creative. Goods and services products continue to emerge, the competition of business people who want to win the market by using advertising is getting tighter, it certainly becomes its own demands for business actors to be able to present a creative campaign in order to attract the interest of the audience. Nasi Padang Everyday is a clothing brand that was originally a movement developed as a form of movement for padang rice lovers. Current business competition makes Nasi Padang Everyday must be able to compete with other business people who are also more aggressive in advertising, therefore the right advertising creative strategy is needed in order to win the hearts of the audience. In this study, the author focused on discussing the creative advertising campaign "BLEH SABBATH" which is an advertisement from the launch of a new article launched by Nasi Padang Everyday. The purpose of this study was to find out how the creative strategy of the "BLEH SABBATH" advertising campaign on Instagram. The theory used is the Unique Selling Proposition (USP) theory, this theory is the uniqueness of the products we offer to consumers so that the product has more value than other products. The uniqueness of such products should be compared with other products in the same product category. This uniqueness will later become the hallmark of the product. The method used in this research is a qualitative method with a case study approach. The data source comes from in-depth interviews and documentation. In this case the subject of the study is the party involved in the creation of the advertisement "BLEH SABBATH". From the results of research that has been done, the author obtained that the key to good advertising planning is a mature creative brief. At the time of creative brief discussed in depth about the location set, the availability of supporting tools, to the talent that plays a role in advertising. It was also found that the selection of slice of life visual techniques in an advertisement is able to encourage the audience or prospective consumers to be interested in the product or brand because indirectly there is an emotional approach taken by the brand, which makes the audience feel represented by their feelings. The element of humor is also important in an advertisement because humor itself can be a refreshment for the audience that will have an impact on the brand image itself. Abstrak. Di abad ke-21 ini khususnya para pelaku usaha dituntut untuk dapat mengikuti perkembangan zaman, inovatif, dan kreatif. Produk barang dan jasa terus bermunculan, persaingan pelaku bisnis yang ingin memenangkan pasar dengan menggunakan iklan semakin ketat, hal tersebut tentunya imenjadi tuntutan tersendiri bagi para pelaku usaha untuk dapat menyajikan sebuah campaign yang kreatif agar dapat menarik minat audiens. Nasi Padang Everyday adalah sebuah brand pakaian yang pada awalnya adalah sebuah movement yang dikembangkan sebagai bentuk pergerakan bagi para pecinta nasi padang. Persaingan bisnis saat ini membuat Nasi Padang Everyday harus mampu berkompetisi dengan pelaku bisnis lainnya yang ijuga semakin agresif dalam beriklan, maka dari itu diperlukan strategi kreatif iklan yang tepat agar dapat memenangkan hati audiens. Dalam penelitian ini penulis berfokus membahas tentang kampanye kreatif iklan “BLEH SABBATH” yang merupakan iklan dari peluncuran artikel baru yang diluncurkan oleh Nasi Padang Everyday. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana strategi kreatif kampanye iklan “BLEH SABBATH” di Instagram. Teori yang digunakan adalah teori Unique Selling Proposition (USP), teori tersebut merupakan keunikan-keunikan dari produk yang kita tawarkan kepada konsumen agar produk tersebut mempunyai nilai lebih dari produk lain. Keunikan produk tersebut harus dibandingkan dengan produk lain dalam satu kategori produk yang sama. Keunikan ini nantinya akan menjadi ciri khas dari produk tersebut. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus. Sumber data berasal dari wawancara mendalam dan dokumentasi. Dalam hal ini subjek penelitian adalah pihak yang terlibat dalam pembuatan iklan “BLEH SABBATH”. Dari hasil penelitian yang telah dilakukan, penulis memperoleh bahwa kunci dari perencanaan iklan yang baik adalah creative brief yang matang. Pada saat creative brief dibahas secara mendalam mengenai set lokasi, ketersediaan alat-alat penunjang, hingga talent yang berperan dalam iklan. Ditemukan juga bahwa pemilihan teknik visual slice of life dalam sebuah iklan mampu mendorong audiens atau calon konsumen untuk tertarik dengan produk atau brand karena secara tidak langsung ada pendekatan emosional yang dilakukan brand yaitu membuat audiens merasa terwakili perasaannya. Unsur humor juga termasuk hal penting dalam sebuah iklan karena humor itu sendiri dapat menjadi refreshment bagi audiens yang akan berdampak pada brand image itu sendiri.